National comparison of the performance of the federal education network in the SAEB of 2013 and 2015 (Research, Society and Development, 2022)
Large-scale assessments are characterized by being external assessments that have different purposes and procedures in relation to assessments carried out by teachers in the classroom. Among these purposes are the certification of students' school levels, carrying out a general diagnosis in some specificities and building a parameter for public policies. In 2016, without warning, the federal government omitted most of the educational institutions of the Federal Network in the ENEM ranking carried out in 2015, which was widely publicized by private institutions. After demands from organizations that represent the network, the government released the ranking with the Federal Network. In view of these facts, the guiding question of this research arises: What is the performance of the Federal Network in the SAEB assessments? To answer this question, the objective of the research carried out was to analyze the performance of national education networks at the national, regional, geo-economic and state levels, still with some positive and negative highlights in the performance by municipality. To this end, a survey of microdata from 1995 to 2015 made available by the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP) was carried out, in which it was only possible to use microdata from 2013 and 2015. Federal Network in relation to other networks in almost all investigated extracts.